Seismic activity on the territory of Slovakia in 2017 - KYSEL, Róbert; CIPCIAR, Andrej; CHOVANOVÁ, Zuzana; CSICSAY, Kristián; FOJTÍKOVÁ, Lucia; KRISTEK, Jozef (Contributions to Geophysics and Geodesy, 2019)
The National Network of Seismic Stations of Slovakia (NNSS) consists of eight short period and five broadband permanent seismic stations and a data centre located at the Earth Science Institute of the Slovak Academy of Sciences (ESI SAS). The NNSS recorded and detected 10 719 seismic events from all epicentral distances in 2017. Totally 73 earthquakes originated in the territory of Slovakia in 2017. This paper provides basic information on the configuration of the NNSS, routine data processing, seismic activity on the territory of Slovakia in 2017 as well as macroseismic observations collected in 2017.